Protein expression profiling of the Drosophila Fragile X mutant brain reveals up-regulation of monoamine synthesis. - Zhang, Y.Q.; Friedman, D.B.; Wang, Z.; Woodruff, E.; Pan, L.; O'donnell, J.; Broadie, K. (Molecular and Cellular Proteomics, 2005)
Fragile X syndrome is the most common form of inherited mental retardation, associated with both cognitive and behavioral anomalies. The disease is caused by silencing of the fragile X mental retardation 1 (fmr1) gene, which encodes the mRNA-binding, translational regulator FMRP. Previously we established a disease model through mutation of Drosophila fmr1 (dfmr1) and showed that loss of dFMRP causes defects in neuronal structure, function, and behavioral output similar to the human disease state. To uncover molecular targets of dFMRP in the brain, we use here a proteomic approach involving two-dimensional difference gel electrophoresis analyses followed by mass spectrometry identification of proteins with significantly altered expression in dfmr1 null mutants. We then focus on two misregulated enzymes, phenylalanine hydroxylase (Henna) and GTP cyclohydrolase (Punch), both of which mediate in concert the synthetic pathways of two key monoamine neuromodulators, dopamine and serotonin. Brain enzymatic assays show a nearly 2-fold elevation of Punch activity in dfmr1 null mutants. Consistently brain neurochemical assays show that both dopamine and serotonin are significantly increased in dfmr1 null mutants. At a cellular level, dfmr1 null mutant neurons display a highly significant elevation of the dense core vesicles that package these monoamine neuromodulators for secretion. Taken together, these data indicate that dFMRP normally down-regulates the monoamine pathway, which is consequently up-regulated in the mutant condition. Elevated brain levels of dopamine and serotonin provide a plausible mechanistic explanation for aspects of cognitive and behavioral deficits in human patients.